Democratic resilience or retreat? A cross-area analysis - Berg-Schlosser, Dirk (Frontiers in Political Science, 2025)
Forms of democratic backsliding can be observed in many parts of the world. However, some conclusions are overly sweeping or alarmist. A detailed case-based regional analysis reveals distinct patterns in this regard. This study highlights some recent findings from a longitudinal international research project, the Transformation Research Initiative “(TRI), which is now based at the Center for Research on Democracy (CREDO) at Stellenbosch University, South Africa. The project involves country and regional experts from all major world areas. The results presented here are derived from the Varieties of Democracy “(V-Dem) data at the macro level, World Values Surveys” (WVS) data on the micro level, and selected case studies. Only a few key findings can be presented here. For a detailed account, see van Beek (ed., 2022).